Analysis of Optimal Power Flow Formulations for HVAC and VSC-HVDC Transmission Networks - Melchor, J. N.G. [UNESP]; Romero, Rubén [UNESP]; Mancarella, P. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The Optimal Power Flow (OPF) problem has been widely studied by researchers and electric industry practitioners for many years. Most of these studies use DC power flow equations to represent the transmission system. However, future power systems will have to deal with new challenges, including integration of renewable energy resources, HVDC links, FACTS devices, etc. The DC formulation may not be appropriate to comprehensively model the behaviour of the new system, for which AC formulations might be required. In this paper, the integration of point-to-point and multi-terminal VSC-HVDC in three nonlinear and DC OPF formulations is analysed using three different test systems. The Knitro and CPLEX solvers are used as optimisation tools. The results show that the generation dispatch resulting from the DC formulation could overload the VSC-HVDC and HVAC transmission branches in the real operation. Moreover, it is demonstrated that the nonlinear formulations can produce good quality solutions that preserve the secure operation of the transmission system.
Keywords: Mathematical model; nonlinear constraints; optimal power flow; power transmission; VSC-HVDC